KULTUR MINORITAS DALAM PERSPEKTIF PENDIDIKAN ISLAM - Makbuloh, Deden (Analisis: Jurnal Studi Keislaman, 2012)
Minority is a concept that implies discrimination;  and it’s absolutely in contrast to the ideals of the nation that has been formulated in the 1945 Indonesian  Constitution.  As long as the use of this concept of minority is at the opposite of the majority, the problem of humanity will could never be resolved properly. Because, the term of minority, in any field, is very strongly colored of discriminatory meaning. Here, author argues that one of the platform to solve such problems of minorities is through understanding of the values developed in Islamic education. Islamic education  growing in the modern era is basically aimed at building a just, prosperous, and high dignity of people and society; and all human being are placed in the same position as the servant of Allah the almighty. So, any society with all their characters engage in the same position of a subject in education. Thus, human empowerment in the Islamic education paradigm has to be carry out in a fair way without any separation and discrimination between minority and majority.